Volunteering among Older Lesbian and Gay Adults: Associations with Mental, Physical and Social Well-Being. (January 2021) - Lyons, Anthony; Alba, Beatrice; Waling, Andrea; Minichiello, Victor; Hughes, Mark; Fredriksen-Goldsen, Karen I.; Edmonds, Samantha; Blanchard, Michelle; Irlam, Corey
Objectives: Volunteering is associated with positive well-being among older people, providing opportunities to stay active and socially connected. This may be especially relevant for older lesbian and gay people, who are less likely than heterosexual people to have a partner, children or support from their family of origin.Methods: Patterns of volunteering and mental, physical and social well-being were examined in a sample of 754 lesbian and gay adults in Australia aged 60 years and older who completed a nationwide survey.Results: Volunteers reported greater positive mental health than non-volunteers. Among the gay men, volunteers additionally reported higher self-rated health and social support and lower psychological distress. Both the lesbian women and gay men who volunteered for lesbian, gay, bisexual, transgender or intersex (LGBTI) organisations also reported greater LGBTI community connectedness than volunteers for non-LGBTI organisations.Discussion: These findings provide further insight into potential factors associated with the well-being of older lesbian and gay adults.